Improving bioenergy recovery from municipal wastewater with a novel cloth-filter anaerobic membrane bioreactor - Martins-West, Neriamara; Martin-Ryals, Ana; Maxwell, Bryan; Schideman, Lance (Frontiers in Bioengineering and Biotechnology, 2023)
Anaerobic membrane bioreactors (AnMBR) have been used for treating high-strength industrial wastewater at full-scale and the potential to use them for mainstream municipal wastewater treatment presents an important opportunity to turn energy-intensive plants into net-energy producers. However, several limitations of the AnMBR technology have prevented their adoption in the municipal wastewater industry, namely high membrane cleaning energy demand and low membrane flux. This study demonstrated a novel AnMBR configuration that uses a commercially available cloth filter technology to address the key limitations of cleaning energy and membrane flux. The cloth filter anaerobic membrane bioreactor (CFAnMBR) is comprised of an anaerobic fixed-film bioreactor coupled with a cloth filter membrane with nominal pore size of 5 µm. The pilot CFAnMBR was operated for 150 d through the winter at a municipal wastewater plant in central Illinois (minimum/average influent temperature 5/13°C). The CFAnMBR increased membrane flux by more than 2 orders of magnitude (3,649 ± 1,246 liters per meter squared per hour) and reduced cleaning energy demand by 78 -92% (0.0085 kWh/m 3 ) relative to previously reported AnMBR configurations. With the CFAnMBR, average COD and TSS removal were 66 and 91%, respectively, and were shown to be increased up to 88% and 96% by in-line coagulant dosing with ferric chloride. Average headspace methane yield was 154 mL CH4/g CODremoved by the end of the study period with influent temperatures of 11± 4°C. The CFAnMBR resolves major limitations of AnMBR technology by employing a commercially-available technology already used for other municipal wastewater treatment applications.